Investigating Student's Learning Style in Learning Activity during Blended Learning Class - Yudi Hari Rayanto; Daryono (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
Applying technology in teaching and learning activity must be arranged, and vividly combined with the expertise of lecturer/teacher since they have a lot of experience in conventional ways in the classroom. It means that in one time lecturer lectures in online, and in other time is through offline (classroom). This combination can be said as a blended learning. Theoretically, visual, auditory, and kinesthetic are kinds of students learning style. Moreover, this research is taken place to seek the truly learning style existed and its affection on student’s achievement. This research is conducted in English Department of Pedagogy and Psychology Faculty at PGRI Wiranegara University. The total number of respondents in this research is 37 students. This research uses qualitative methods whereas the research design used is descriptive. There are three kinds of instruments used, they are; questionnaire, observation, and documentation. Based on the result of an analysis through questionnaire found that there are 6 kinds of learning style, they are;3 students are in visual learning style, 7 students are kinesthetic learning style, 8 students are visual-auditory learning style, I student is auditory-kinesthetic learning style, 10 students are invisual-kinesthetic learning style, and 8 students are in visual-auditory-kinesthetic learning style. Meanwhile, from the data gained through documentation as the test form indicates that the group of students with three visual-auditory-kinesthetic learning style had a higher total score with a total score of 432 with an average score of 86,4, secondly, a group of students with kinesthetic learning style who got a total score of 431 with an average score of 86,2, and the third was with a total score of 340 with an average score of 85 was a group of students with visual-auditory learning style. So, it can be concluded that the more learning style existed in a student, the more score is obtained.